Wheat Alkylresorcinols Suppress High-Fat, High-Sucrose Diet-Induced Obesity and Glucose Intolerance by Increasing Insulin Sensitivity and Cholesterol Excretion in Male Mice. Issue 2 (26th November 2014) - Oishi, Katsutaka; Yamamoto, Saori; Itoh, Nanako; Nakao, Reiko; Yasumoto, Yuki; Tanaka, Keiko; Kikuchi, Yosuke; Fukudome, Shin-ichi; Okita, Kimiko; Takano-Ishikawa, Yuko
Abstract: Background: Epidemiologic studies have shown that the consumption of whole grains can reduce the risk of type 2 diabetes mellitus, cardiovascular disease, and all-cause mortality. However, the underlying mechanisms remain a matter of debate. Objective: We aimed to determine the effects of wheat bran–derived alkylresorcinols on diet-induced metabolic disorders in mice. Methods: We fed C57BL/6J mice a normal refined diet or a high-fat, high-sucrose diet [29.1% fat, 20.7% protein, 34.0% carbohydrates containing 20.0% sucrose (w/w)] alone (FS) or containing 0.4% (wt:wt) alkylresorcinols (FS-AR) for 10 wk. Results: The alkylresorcinols suppressed FS-induced increases in body weight by 31.0% as well as FS-induced hepatic triglyceride accumulation (means ± SEMs: 29.6 ± 3.18 and 19.8 ± 2.42 mg/g tissue in the FS and FS-AR groups, respectively), without affecting energy intake. We measured circadian changes in blood metabolic hormones and found that FS-induced hyperinsulinemia (5.1 and 2.1 μg/L at night in the FS and FS-AR groups, respectively) and hyperleptinemia (21.6 and 10.8 μg/L at night in the FS and FS-AR groups, respectively) were suppressed by alkylresorcinols. Glucose and insulin tolerance tests showed that alkylresorcinols significantly reduced fasting blood glucose concentrations (190 ± 3.62 and 160 ± 8.98 mg/dL in the FS and FS-AR groups, respectively) and suppressed glucose intolerance as well as insulin resistance induced by the FS diet. Furthermore, alkylresorcinols significantly increased insulin-stimulated hepatic serine/threonine protein kinase B phosphorylation compared to the FS diet (+81.3% and +57.4% for Ser473 and Thr308, respectively). On the other hand, pyruvate and starch tolerance tests suggested that alkylresorcinols did not affect gluconeogenesis and carbohydrate digestion, respectively. Alkylresorcinols significantly increased fecal cholesterol excretion by 39.6% and reduced blood cholesterol concentrations by 30.4%, while upregulating the expression of hepatic cholesterol synthetic genes such as sterol regulatory element binding protein 2 ( Srebf2 ) and 3-hydroxy-3-methylglutaryl-Coenzyme A synthase 1 ( Hmgcs1 ). Conclusions: These findings suggest that wheat alkylresorcinols increase glucose tolerance and insulin sensitivity by suppressing hepatic lipid accumulation and intestinal cholesterol absorption, which subsequently suppresses diet-induced obesity in mice.